Unveiling Antibiotic Stewardship in the ICU: A Cross-Sectional Study on Knowledge and Practices among Healthcare Professionals in Pakistan - Sajjad Ansari, Kaswer; Shahid Nawaz, Fawzia; Gul, Momy; Sana, Fatima; Bakhtawar, Faiz; Majeed, Kaukab (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess and compare the understanding of antimicrobial resistance (AMR) and evaluate the prescribing patterns of antibiotics among healthcare professionals in the intensive care unit (ICU) of a tertiary care hospital in Pakistan.Study Design: Cross sectional study.Place and Duration of Study: Intensive Care Units of Combined Military hospital, Quetta Pakistan, from Feb to Jul 2023.Methodology: Questionnaires were distributed to healthcare workers, including physicians, surgeons, neonatologists, gynecologists, and microbiologists, working in the ICU. Paramedical staff were excluded from the study. Data were collected through Google Sheets and analyzed using SPSS version 27.Results: A total of 221 participants completed the questionnaire, with 82(35.2%) males and 139(59.7%) females. The majority of respondents 124(43.2%) had a bachelor's degree, while 97(41.6%) were postgraduates. The analysis segregated the responses based on the level of qualification and specialty of the participants. The level of education showed little impact on changes in knowledge and practices related to antibiotic stewardship. However, a significant difference (p=0.025) was observed regarding the use of local guidelines for antibiotic prescription. Junior doctors (53%) exhibited a higher inclination towards local procedures, while seniors disagreed.Conclusion: This study revealed that the level of education had limited influence on the knowledge and practices of clinicians regarding antibiotic stewardship in the ICU. However, a significant difference was observed in the use of local guidelines between junior and senior doctors. The majority of participants agreed on the importance of involving microbiologists and organizing regular training sessions and clinical ...